Microbial communities in pre-columbian coprolites. - Tasha M Santiago-Rodriguez; Yvonne M Narganes-Storde; Luis Chanlatte; Edwin Crespo-Torres; Gary A Toranzos; Rafael Jimenez-Flores; Alice Hamrick; Raul J Cano (PLoS ONE, 2013)
The study of coprolites from earlier cultures represents a great opportunity to study an "unaltered" composition of the intestinal microbiota. To test this, pre-Columbian coprolites from two cultures, the Huecoid and Saladoid, were evaluated for the presence of DNA, proteins and lipids by cytochemical staining, human and/or dog-specific Bacteroides spp. by PCR, as well as bacteria, fungi and archaea using Terminal Restriction Fragment analyses. DNA, proteins and lipids, and human-specific Bacteroides DNA were detected in all coprolites. Multidimensional scaling analyses resulted in spatial arrangements of microbial profiles by culture, further supported by cluster analysis and ANOSIM. Differences between the microbial communities were positively correlated with culture, and SIMPER analysis indicated 68.8% dissimilarity between the Huecoid and Saladoid. Proteobacteria, Bacteroidetes and methanogens were found in all coprolite samples. Propionebacteria, Shewanella and lactic acid bacteria dominated in the Huecoid samples, while Acidobacteria, and peptococci were dominant in Saladoid samples. Yeasts, including Candida albicans and Crypotococcus spp. were found in all samples. Basidiomycetes were the most notable fungi in Huecoid samples while Ascomycetes predominated in Saladoid samples, suggesting differences in dietary habits. Our study provides an approach for the study of the microbial communities of coprolite samples from various cultures.